Pemanfaatan SPARQL Dalam Pencarian Data Alih Kredit Merdeka Belajar Kampus Merdeka - Agiharta, Kafka Febianto; Suteja, Bernard Renaldy (Jurnal Teknik Informatika dan Sistem Informasi, 2023)
The Merdeka Belajar Kampus Merdeka (MBKM) program provides facilities for students to transfer credits from work activities to specific courses. To support this process, this research utilizes Semantic Web technology by integrating an ontology built using the Protégé tool. Through the use of SPARQL query language, Semantic Web technology enables efficient and accurate searching between activity descriptions and courses based on the context and semantic meaning of the data. The research results show that this research can retrieve the required information efficiently and accurately from the ontology that has been developed.